Organizational factors of innovativeness in Serbian enterprises - Goran Pitić; Aleksandar Vučković (Naše gospodarstvo / Our Economy, 2021)
This paper analyses correlations between several organizational characteristics and product/process innovations in enterprises in Serbia. We used the World Bank Enterprise Survey data on 339 small, medium, and large companies from various industries. Many of the factors analysed in this study are consistent with theoretical conclusions in the literature on this topic and relate to organizational maturity. Also, factors such as the size of the company and the industry to which it belongs were analysed. For correlations testing, the Chi-square correlation coefficient and the Cramer's V test were used. The analysis revealed correlations between innovativeness and many organizational characteristics. However, in some cases, contrary to theoretical claims, correlations were not confirmed. We found that the introduction of new products and/or processes in the company is influenced by business strategy, production targets, number of performance indicators monitored, establishment of quality management system, formal training programs for company's full-time employees, ease of achieving the company's production targets, level of awareness of management and employees about the company's production targets, spending on research and development activities within the company, and acquisition of external knowledge, way of promoting non-managers in a company, time frame of the company's production targets, company's size and main market.
Keywords: C19; L26; O31; 330; innovativeness; corporate entrepreneurship; correlation analysis; organizational characteristics; Serbia